Demotivating factors and coping strategies among Filipino EFL teachers in Thailand - Christopher Molingit Balintag; Punyapa Saengsri (International Journal of Evaluation and Research in Education (IJERE), 2022)
Teaching demotivation may negatively affect teachers’ performance in English language teaching. This present study investigated the demotivating factors and coping strategies of seven Filipino English as a foreign language (EFL) teacher in Thailand.Using qualitative design, semi-structured interview was used to elicit the views of teachers. Findings have shown five demotivating factors: administration-demotivational factor, colleague-demotivational factor, student-demotivational factor, self-demotivational factor, and parent-demotivational factor. Moreover, self-regulation strategy and pedagogical strategy are useful for the teacher to cope with those factors. Implications were discussed to help foreign EFL teachers in Thailand become aware of teaching challenges in Thailand.